The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1021/ja055534k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Cyclizations in a Nonpolar Solvent Using Molecular Oxygen and Studies on the Stereochemistry of Oxypalladation

Abstract: Oxidative cyclizations of a variety of heteroatom nucleophiles onto unactivated olefins are catalyzed by palladium(II) and pyridine in the presence of molecular oxygen as the sole stoichiometric oxidant in a nonpolar solvent (toluene). Reactivity studies of a number of N-ligated palladium complexes show that chelating ligands slow the reaction. Nearly identical conditions are applicable to five different types of nucleophiles: phenols, primary alcohols, carboxylic acids, a vinylogous acid, and amides. Electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(92 citation statements)
references
References 87 publications
3
86
0
3
Order By: Relevance
“…The stereochemistry of oxidative intramolecular alkoxypalladations was studied [843]. Oxidative intramolecular alkoxy-palladation (formally alkoxy-palladation-␤-elimination) of a pendant alkene was used to form functionalized furans and benzofurans [440,844], dihydropyranones and furanones [845], (−)-15-oxopuupehenol [846], garsubellin A (Eq.…”
Section: Formation Of Carbon-oxygen -Selenium and -Sulfur Bond From mentioning
confidence: 99%
“…The stereochemistry of oxidative intramolecular alkoxypalladations was studied [843]. Oxidative intramolecular alkoxy-palladation (formally alkoxy-palladation-␤-elimination) of a pendant alkene was used to form functionalized furans and benzofurans [440,844], dihydropyranones and furanones [845], (−)-15-oxopuupehenol [846], garsubellin A (Eq.…”
Section: Formation Of Carbon-oxygen -Selenium and -Sulfur Bond From mentioning
confidence: 99%
“…Hence, the energy barriers of the steps occurring after the RDS should be lower than these calculated E a s. The suggestion of H-transfers sequence (Eqs. (6)- (8)) is based on the absence of any deuterium isotope incorporation when the This step has been studied in several cases. The experimental isotopic effects [14,[17][18][19][20] clearly indicate that the bHE step could not be the RDS of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3,5] A large variety of oxygen-containing heterocycles have been obtained with this methodology, [26][27][28][29][30][31][32][33][34] even in an asymmetric fashion. [35][36][37] In our continuing interest in Pd-catalyzed access to substituted THFs and tetrahydropyrans, we were interested in the synthesis of such functionalized oxygen heterocycles. Recently it was reported that ω-hydroxy-α,β-unsaturated alcohols underwent an intramolecular Pd II -catalyzed cycli-zation to give vinyltetrahydropyrans.…”
Section: Introductionmentioning
confidence: 99%